Impact of takeoff angle of bucket type energy dissipater on scour hole - Alias, Nor Azlina; Mohammed, Thamer Ahmed; Ghazali, Abdul Halim; Megat Mohd Noor, Megat Johari (Science Publications, 2008)
Scour holes formed downstream of bucket type energy dissipater may affect the safety and stability of the structure. In this study, a physical model is employed to study the impact of takeoff angle of bucket type energy dissipater on the scour hole. The area of longitudinal profile of the scour hole is used to evaluate the seriousness of the scour at downstream of the bucket type energy dissipater. Experimental results showed that the takeoff angle of 45° is the optimum angle which gives minimum longitudinal area of the scour hole. Also, validation of selected equations for predicting maximum scour depth at downstream of the bucket type energy dissipater showed that the equation proposed by Schoklitsch gave minimum error (33%) [1].